FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN LONG COVID PADA PENINTAS COVID-19 - Yudha Asy'ari (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2022)
Long COVID (also known as post acute COVD, Post-COVID-19, Post-COVID-19 syndrome) are signs and symptoms that are still experienced after passing thorugh the acute phase of COVID-19. Long COVID appears in many COVID-19 survivors. Signs and symptoms experienced by sufferers of Long COVID are very diverse. Ranging from respiratory disorders to cognitive disorders. This study aims to determine the factors associated with the incidence oh Long COVID in COVID-19 survivors in Urban Village of Jatisampurna, Bekasi City. This study used a cross sectional research design. The study was conducted using an online questionnaire. This study was followed by 308 respondents, with proportion of female 64% and male 36%. The results of this study show the proportion of the incidence of Long COVID is 80,2%. The most common symptom reported was fatigue (72.8%), brain fog (30.5%), and dry cough (21.8%). Bivariate analysis showed that there is no significant relationship between age and occupation as health worker with incidencen of Long COVID. However, there is a significant relationship between gender with the incidence of Long COVID (p = 0,011, OR= 2,157) and comorbidity with incidence of Long COVID (p= 0,006, OR= 2,652).